Foreign Body in the Penile Prosthesis Reservoir - Garrido-Abad, Pablo; Sinués-Ojas, Bryan; Martínez-Blázquez, Laura; Conde-Caturla, Pablo; Estévez- Sánchez, Delfina; Fernández-Arjona, Manuel (Urology Journal, 2016)
gg